(untitled) (Bangladesh Journal of Agricultural Research, 2022)
This study evaluated the effect of integrated disease management on the incidence and severity of blast disease, and growth performance of rice. Moringa oleifera extract, Trichoderma asperellum, cattle dung and a synthetic fungicide were evaluated in sixteen treatment combinations using a susceptible IRAT 109 rice cultivar. The pot experiment was laid out in a randomized complete block design with three replications at the rooftop screenhouse of the Department of Crop Protection and Environmental Biology, University of Ibadan between May and October, 2019. Treatment with combination of M. oleifera extract, cattle dung and blastforce had the lowest disease incidence and mean severity of 16.8 and 7.5%, respectively which was significantly (p<0.05) lower than the standard positive check. Inoculated plants that were treated with a combination of T. asperellum, M. oleifera and cattle dung produced the highest yield of 7.6 tons/ha relative to control. This study showed that the combined application of naturally occurring biopesticides and cattle dung was more effective than single treatment in the management of rice blast disease. Bangladesh J. Agril. Res. 45(4): 395-407, December 2020